BENTUK DINAMIKA SOLIDARITAS SOSIAL DALAM MERESPONS TRANSFORMASI BUDAYA PADA MASYARAKAT HINDU DI KOTA MATARAM - Aryanatha, I Nengah (Sekolah Tinggi Agama Hindu Negeri Gde Pudja Mataram, 2019)
This research is intended to conduct a study of the dynamics of social solidarity in response to cultural transformation at Hindu societies in Mataram City, West Nusa Tenggara. The design of this study is descriptive interpretive by focusing on case studies relating to the occurrence of dynamics in a number of aspects of social life. Based on the results of the study it was found that the dynamics of the dimensions of social solidarity in responding to cultural transformation at Hindu societies in Mataram City was indicated by the melting of traditionally patterned social ties, the formation of modern social organizations, the policing of Hindu society on traditionalism and modernism. The occurrence of dynamics in the dimensions of social solidarity is closely related to efforts to respond to the times. This is a manifestation of cultural adaptation, namely adjustments that are assumed to be necessary in order to be able to keep abreast of developments occurring in the surrounding environment. In connection with the results of this study, the dynamics in the dimensions of social solidarity in responding to the cultural transformation of Hindu societies in the city of Mataram as a phenomenon closely related to efforts to adapt to the times should be given space for the necessary adjustments in order to maintain the existence of the system socio-cultural in the midst of the rapid pace of social change. In order to conduct a more holistic study, further research is needed regarding other aspects which are influenced by the dynamics in the dimensions of social solidarity in responding to the cultural transformation of Hindu communities in the City of Mataram, such as economic aspects, political aspects, and others.